Masks and mirrors : Generation X and the chameleon personality - Rosen, Bernard Carl (Praeger, 2001)
As America experiences the growing pains associated with the rapid social changes in the economy, technology, and culture, various groups must develop coping mechanisms to help them deal with the anxiety that is brought on by such changes. Generation Xers, on the cutting edge of these changes, are no exception. More so than any other group, elite Xers, those who are succeeding in the new economy, have adopted a unique personality style, chameleonism, as a defense mechanism. People with a chameleon personality pretend to be what others want them to be in an effort to obtain for themselves the kind of security Xers feel previous generations have enjoyed, but which may not be available to their own generation. This examination of the Xer generation sheds new light on the survival mechanisms employed by those who feel threatened by social changes, even as they participate in and benefit from them.